Testing a conceptual Hierarchy of Effects model of food marketing exposure and associations with children and adolescents' diet-related outcomes - Bridget Kelly; Emma Boyland; Mimi Tatlow-Golden; Paul Christiansen (Cambridge University Press, 2024)
Abstract Objective: Children's exposure to unhealthy food marketing contributes to poor diets by influencing the foods that children like, request, buy and consume. This study aimed to use confirmatory mediational analyses to test a hypothetical model of marketing effects, to better understand the mechanisms behind food marketing's impacts on children. Design: Children responded to a cross-sectional online survey about their attitudes towards, and purchase and consumption behaviours of, ten frequently promoted food/beverage brands and their media use. Structural equation modelling tested a priori potential pathways for the effects of food marketing exposure on children's diets. Participants: 10-16-year-old children (n 400). Setting: Australia. Results: There was a significant positive correlation between children's commercial screen media use and their attitudes towards brands (related to perceived social norms) and their brand purchasing behaviours, including their own purchases and requests to parents. The use of strategies to avoid advertising in commercial screen media reduced but did not remove the association between media use and brand purchases. Other brand exposures (on clothing, outdoor advertising, sponsorships) had a positive association with children's perceived social norms about brands and their brand purchases and requests. Non-commercial screen media use was not associated with any brand-related outcomes. Conclusions: Commercial screen media use and other brand exposures were strongly positively associated with children's perceptions and purchasing behaviours of frequently marketed food/beverages. Regulations to restrict children's exposures to food marketing on-screen and through other media are required to reduce the effect of marketing exposure on children's food purchasing behaviours.